PENERAPAN PROJECT BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN FIQIH DI MA NURUL IKHWAN MAROS - Irfandi; Anwar, M. Yunus; Surani; Nurlaelah; Sampurno, Bambang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students' learning outcomes in the Fiqh subject through the implementation of the Project Based Learning (PjBL) model at MA Nurul Ikhwan Maros. The research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, consisting of two cycles: planning, action, observation, and reflection. The participants were 34 eleventh-grade students of MA Nurul Ikhwan Maros. Data were collected through observation, interviews, learning achievement tests, and documentation. The collected data were analyzed using qualitative descriptive and quantitative descriptive techniques. The findings revealed that the implementation of the Project Based Learning model significantly improved students' learning outcomes. Learning mastery increased from 29.42% in the pre-cycle, with an average score of 69.55, to 67.64% in Cycle I, with an average score of 80.44, and further increased to 97.05% in Cycle II, with an average score of 88.67. In addition, the implementation of Project Based Learning enhanced students' participation, collaboration, critical thinking, and engagement in the learning process. Therefore, the Project Based Learning model proved effective in improving students' learning outcomes in the Fiqh subject at MA Nurul Ikhwan Maros.